BIODIVERSITY AND HABITAT PREFERENCES OF LIVING SHARKS IN THE SOUTHEAST ASIAN REGION - Ahmad Bin Ali; Fahmi Fahmi; Dharmadi Dharmadi; Tassapon Krajangdara; Annie Lim Pek Khiok (Indonesian Fisheries Research Journal, 2018)
This paper reviews the biodiversity and habitat preferences of living sharks in the Southeast Asian region accumulated from published literatures including journals, books, proceedings, unpublished technical papers, and technical reports as well as authors’ knowledge and experiences working in this field. A total of 196 species of sharks from nine orders and 30 families have been recorded inhabiting from fresh water to deep ocean in this region. Indonesia recorded the highest diversity with 114 species from 27 families followed by the Philippines with 96 species (27 families), Thailand 76 species (21 families), Vietnam 70 species (23 families), Malaysia 68 species (19 families), Myanmar 64 species (19 families), Brunei Darussalam 45 species (15 families), and Cambodia with 26 species from 10 families. Many species still need to be confirmed and are most probably new species. In term of habitat preferences, 83 species of sharks (42.3%) inhabit continental/insular shelves (SHL) followed by continental/insular slopes (SLO) with 48 species (24.5%), shelf to slope (SHS) with 26 species (13.3%), and shelf to oceanic (SHO) with 16 species (8.2%). Only nine species (4.6%) inhabit oceanic and six species (4%) obligate freshwater and euryhaline freshwater/shelves.